The implications of non-authentic questions in Galatians - P. Verster (Acta Theologica)
A new classification of non-authentic questions is helpful in understanding the way in which Paul uses persuasion in Galatians. Paul uses many non-authentic questions, and the implications thereof are evident in the type of question used. The way in which he violates the maxims identified by Grice also entails certain implications which can be used to establish the meaning of certain passages. Questions used in Galatians include statements, empty statements, emphatic rhetorical interrogatives, ironical interrogatives and appeal questions. Paul often violates the rule of politeness in order to emphasise his point.